Analisa Performansi Trafik Multimedia Pada Pemodelan Jaringan VPN Menggunakan Metode CLSA - Batubara, Aldi Kurniawan; Sari, Linna Oktaviana (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Network modeling is a way that must be learned by anyone who wants to build a network, either from the type of topology, or software that will be used. In designing a computer network based on Virtual Private Network (VPN), a networker's must have techniques or methods that are network management, so that the network can be made according to need. Network management recommended by Cisco is the Cisco Lifecycle Service Approach (CLSA) method, which manages the network until the redesign stages without changing the direction of the project's objectives. The purpose of making VPN network modeling is to see the effect of topology differences, multimedia traffic and the number of users. The design uses GNS3 v2.0.3 and VirtualBox software, where GNS3 allows complex network simulations, because it uses the original operating system from a network device such as cisco so that the computer can function like a router or even a switch. In designing this network the measuring value to be in use is throughput, delay, packet loss and jitter. Scenario testing using star topology, then do 3 multimedia traffic conditions and use the condition 1 client and 2 client. From star topology test with 3 multimedia traffic, the average delay obtained at 1 client is 34,53 ms and at 2 client equal to 57,76 ms, the average jitter obtained at 1 client is 75,2 ms and at 2 client of 114.5 ms, where the delay result <150 ms (millisecond) is categorized good according to ITU-T G.107 10 06/2015. While the average throughput obtained at 1 client of 0.150 Mbits/sec and at 2 clients of 0.283 Mbits/sec, the results obtained are categorized fairly well according to ITU-T X.135 08/97 with a good categorization of 0.628 Mbits/sec. For packet loss obtained at 0%, where the packet loss < 1% is categorized good according to ITU-T G.1010 11/2001.Keyword : VPN, QoS, CLSA, GNS3 v2.0.3, VirtualBox